Legal Analysis of the Prohibition of Interfaith Marriages Based on Pancasila and the State Constitution Republic of Indonesia in 1945 - Muhamad Aksan Akbar (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
The existence of Law no. 1 of 1974 concerning Marriage still leaves problems for couples of different religions who want to get married. Some groups view the prohibition of interfaith marriages as contrary to human rights. This research aims to find out whether the prohibition on marriage between interfaith couples in Indonesia is contrary to the values ​​of Pancasila and the provisions in the 1945 Constitution and what the legal implications are for marrying interfaith couples in Indonesia. This research method is normative. The results of the research are that the prohibition on marriage between interfaith couples in Indonesia does not conflict with the values ​​of Pancasila and human rights in the 1945 Constitution. State intervention in the implementation of marriage is carried out to ensure that the implementation of marriage is in accordance with the provisions of each religion and belief, so that the rights of citizens in worshiping according to one's religion and beliefs can be protected. The enactment of Article 2 of the Marriage Law is not intended to hinder the freedom to embrace religion and belief, freedom to embrace religion and belief remains the right of every citizen as stipulated in the 1945 Constitution. Psychologically, interfaith marriages can have implications for household happiness, while from a legal aspect they have implications for the validity of marriage, the status of children and inheritance issues..